Comparative and phylogenetic analyses of the chloroplast genomes of mangrove plants - Jigui Yuan; Wei Gu; Haijie Yang; Mei Wang (Scientific Reports)
Abstract Mangrove ecosystems play a crucial role in coastal environment by stabilizing shorelines, reducing erosion, and providing habitat for diverse wildlife. However, there are fewer studies on the genetic management of mangrove plants. In this study, the chloroplast genome of Hibiscus tiliaceus L. was obtained through whole genome resequencing. The complete chloroplast genome of this species was 161,764 bp in length and comprised 84 protein-coding genes, eight rRNA (ribosomal RNA) genes, 37 tRNA (transfer RNA) genes. We conducted a comparative analysis of the chloroplast genomes of 26 mangrove species and found the conservation of genome structure among these mangrove plants, including the number of protein-coding genes, rRNA genes, and tRNA genes. However, there were noticeable differences in the number of SSRs (simple sequence repeats), the number of repeat sequences, and the borders of the IR (inverted repeat) regions, indicating genetic differentiation among mangrove plants. Besides, we found special differences in the distribution of certain genes in chloroplast genomes of certain species. Moreover, phylogenetic analysis based on chloroplast genome data clearly revealed that neither true mangrove plants nor semi-mangrove plants were monophyletic. These results revealed that chloroplast genomes will be useful to help understand the genetic differentiation and phylogenetic relationships of mangrove plants, which could assist in the genetic management, conservation, and restoration of mangrove ecosystems.